The effect of combined exercises (Physical - skill) on some physical abilities and the accuracy of the handball jumping shooting skill - Assistant teacher. Duaa Alaa Manea (Global Scientific Publishing, 2024)
As they constitute major goals in preparation and preparation for physical preparation for sports games, and that one of the requirements of the special physical preparation period in the game of handball is the development of its physical capabilities in order to integrate them in the player and prepare him for the stage of competitions. The importance of the research lies in that compound exercises help the player to perform movements under Variable and different circumstances, so that the player is able to face the various circumstances and situations that the player is exposed to during the match well, in addition to developing the skill of aiming by jumping with the handball. The problem of the research was through the researcher’s observation of Training of some handball teams in Dhi Qar Governorate: I noticed a lack of interest in modern methods of training, so the researcher decided to study this problem by developing complex exercises to develop some physical abilities and the accuracy of the jumping shooting skill, which would raise the level of handball shooting towards the best. As for the objectives of the research Preparing combined exercises (physical - skill) to develop some physical abilities and the accuracy of the skill of aiming from jumping with handball, and identifying the statistical differences between the pre- and posttests for the control and experimental groups in some physical abilities and the accuracy of the skill of aiming from jumping with handball, and identifying the statistical differences between Posttests for the control and experimental groups on some abilities Physical abilities and the accuracy of the aiming skill from jumping with the handball, and the research hypotheses are that there are jumping with the handball and in favor of the post-tests, and there are statistically significant differences between Posttests between the control and experimental groups on some physical abilities and the accuracy of the skill of aiming from jumping with handball, in favor of the experimental group.
Keywords: exercises; aiming; between; favor